4n-5(n+2)=7-3(3-n)

Simple and best practice solution for 4n-5(n+2)=7-3(3-n) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4n-5(n+2)=7-3(3-n) equation:


Simplifying
4n + -5(n + 2) = 7 + -3(3 + -1n)

Reorder the terms:
4n + -5(2 + n) = 7 + -3(3 + -1n)
4n + (2 * -5 + n * -5) = 7 + -3(3 + -1n)
4n + (-10 + -5n) = 7 + -3(3 + -1n)

Reorder the terms:
-10 + 4n + -5n = 7 + -3(3 + -1n)

Combine like terms: 4n + -5n = -1n
-10 + -1n = 7 + -3(3 + -1n)
-10 + -1n = 7 + (3 * -3 + -1n * -3)
-10 + -1n = 7 + (-9 + 3n)

Combine like terms: 7 + -9 = -2
-10 + -1n = -2 + 3n

Solving
-10 + -1n = -2 + 3n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-3n' to each side of the equation.
-10 + -1n + -3n = -2 + 3n + -3n

Combine like terms: -1n + -3n = -4n
-10 + -4n = -2 + 3n + -3n

Combine like terms: 3n + -3n = 0
-10 + -4n = -2 + 0
-10 + -4n = -2

Add '10' to each side of the equation.
-10 + 10 + -4n = -2 + 10

Combine like terms: -10 + 10 = 0
0 + -4n = -2 + 10
-4n = -2 + 10

Combine like terms: -2 + 10 = 8
-4n = 8

Divide each side by '-4'.
n = -2

Simplifying
n = -2

See similar equations:

| 67+92x=92 | | 2/4+2/4+x=3 | | 4/3=5/8a+14/3 | | -5x-3(3x+10)=138 | | -3(2x-3)=4(5-x) | | 2(3z-1)=16 | | 3(x-8)=7 | | 3x+8x-14=30 | | 3(x-4)+37=2x | | 1.3y+7.8=1.3 | | 5x-6=5*5+3 | | -4w+4=0 | | 6x+2-3x+9=0 | | x/2+x/3*4=5 | | -2x-6(3x+10)=40 | | 14+2y=2(y+3) | | (5x-4)(3x+2)=0 | | 100+10=x+15 | | 7(x+4)+8=8(2x-6) | | 5r=16-(2r+8) | | 9-x+2=2x+3x | | 4x-4(x+4)=5(x+4) | | 2(3(-3)-2)+-3=9 | | (3x-5)(9x+7)=0 | | 2x-5(3x-8)=118 | | 7x+8-10x-12=9x-6x+8 | | 10(2x-4)+20=5(4x-3)+18+3x | | 6a+7-a=-17 | | -4(2x-3)=4x-18+3x | | 1/3X^2+4X+1=0 | | 6s-10=s-2 | | x^2-24x-64=0 |

Equations solver categories